Synthesis Of Al2o3 Thin Film As Thermal Interface Materials (Tims) Using Chemical Vapor Deposition (Cvd) Method For Solid State Lighting Applications - Lim, Wei Qiang (2018)
Continuous efforts by researchers have improved the design and overall light output of the SSL devices yet there are concerns still remain regarding the reliability of devices under certain circumstances. The rise in driving current would lead to an increase in light output and junction temperature within the devices simultaneously. An excessive rise in junction temperature can cause thermal runaway and affect devices lifetime, ultimately leading to devices failure. Thus, a highly sophisticated thermal management system is needed to compensate with the high performance of SSL devices. In this project, thin film coating technique has been suggested as one of the effective approaches in improving the thermal dissipation system at system level.